Printed-Circuit-Board-Based Two-Electrode System for Electronic Characterization of Proteins - Talebi, Sara; Daraghma, Souhad M.A.; Ramesh, Subramaniam; Bhassu, Subha; Gnana Kumar, Georgepeter; Periasamy, Vengadesh (American Chemical Society, 2020)
Proteins have been increasingly suggested as suitable candidates for the fabrication of biological computers and other biomolecular-based electronic devices mainly due to their interesting structure-related intrinsic electrical properties. These natural biopolymers are environmentally friendly substitutes for conventional inorganic materials and find numerous applications in bioelectronics. Effective manipulation of protein biomolecules allows for accurate fabrication of nanoscaled device dimensions for miniaturized electronics. The prerequisite, however, demands an interrogation of its various electronic properties prior to understanding the complex charge transfer mechanisms in protein molecules, the knowledge of which will be crucial toward development of such nanodevices. One significantly preferred method in recent times involves the utilization of solid-state sensors where interactions of proteins could be investigated upon contact with metals such as gold. Therefore, in this work, proteins (hemoglobin and collagen) were integrated within a two-electrode system, and the resulting electronic profiles were investigated. Interestingly, structure-related electronic profiles representing semiconductive-like behaviors were observed. These characteristic electronic profiles arise from the metal (Au)-semiconductor (protein) junction, clearly demonstrating the formation of a Schottky junction. Further interpretation of the electronic behavior of proteins was done by the calculation of selected solid-state parameters. For example, the turn-on voltage of hemoglobin was measured to occur at a lower turn-on voltage, indicating the possible influence of the hem group present as a cofactor in each subunit of this tetrameric protein. Copyright © 2020 American Chemical Society.